Perancangan dan Implementasi Produk UMKM Aplikasi Vegetarian “VegeYuk” Berbasis Android - Robi Robi; Yonky Pernando (TIN: Terapan Informatika Nusantara, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy. In today's digital era, Android technology has become a highly useful tool for promoting products and providing services to users. This research aims to develop an Android application called "VegeYuk" specifically designed to support MSMEs that primarily focus on vegetarian products. The VegeYuk application is built using Android Studio for software development and Figma for designing the user interface. The development approach used in this project is the Waterfall method, which involves structured stages from planning, analysis, design, implementation, testing, to delivery. The primary objectives of the VegeYuk application are twofold. First, it aims to assist MSMEs that focus on vegetarian products in efficiently promoting their products through the popular Android platform. Second, it provides an easy ordering service for users who wish to purchase vegetarian products. The application enables sellers to market their products easily through clear product images, descriptions, and prices. On the other hand, users can quickly find the vegetarian products they are looking for and place orders effortlessly. In an era where awareness of the importance of healthy and sustainable eating habits is increasing, the VegeYuk application has the potential to become a valuable tool for vegetarian MSMEs and users who want to adopt a vegetarian lifestyle. With this application, it is expected that vegetarian MSMEs can grow and gain greater exposure, while users can easily embrace a healthier lifestyle through vegetarian food choices.